THE CONCEPTIONS OF GLOBALIZATION: THE SYNERGETIC APPROACH - Утаві, Алі Абдулкарім (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
Globalization is the phenomenon that now acquires the properties of self-organizing systems. The features of such systems are unstable, unpredictable, invariance behavior, constant deviation from equilibrium. Application to the analysis of this synergistic approach justifies and defines pluralism of scientific research that determines a harmonious combination of positions scholars of East and West in the understanding and perception of this controversial phenomenon.